Neuro-Architecture: Design Principles and Scientific Visualization - Akbal, Beyza Nur; Burkut, Emine Banu; Yılmaz, Nazende (Akademisyen Yayınevi, 2025)
Neuroarchitecture is an architectural principle that combines neuroscience and architecture. Neuroarchitecture examines the physical and psychological responses of users to space and the environment (Eberhard, 2009; Ritchie, 2020). Neuroarchitecture aims to produce spatial designs in response to these responses and to enhance individual psychological processes. Space design and environmental factors significantly influence human perception, mood, and behavior. Individuals interact with their environment, exhibiting responses based on sensory, physical, and past experiences. A person’s past memories and traumas influence their perception of space. This research examines neuro-architecture conceptually and theoretically. The study utilizes the scientific mapping method, a quantitative research method. This method reveals the conceptual, theoretical, and evolutionary development of the relevant literature through numerical data and frequencies. The findings of the research facilitate the emergence of influential publications on neuro-architecture in the current literature.